Livestock and livelihoods webinar series: Leveraging livestock to combat malnutrition - International Livestock Research Institute (International Livestock Research Institute, 2021)
Part of the ILRI and Venture 37 Livestock and Livelihoods webinar series, this recording shares perspectives from East Africa on the role of the livestock sector in enhancing food security and nutrition in Africa. It was recorded on 7 July 2021.